Spontaneous Rupture, Disappearance, and Reaccumulation of a Rathke's Cleft Cyst - Katrina Maniec; Joe C. Watson (Case Reports in Endocrinology)
Rathke's cleft cysts (RCCs) are benign epithelium-lined intrasellar cysts containing mucoid material and are believed to originate from the remnants of Rathke's pouch. Most are asymptomatic but may cause symptoms secondary to compression of adjacent structures such as visual disturbances and endocrinopathies, especially hypopituitary. Furthermore, inflammation such as an aseptic meningitis syndrome may be associated with these tumors, presumably resulting from leakage of cyst material into the subarachnoid space. We present a unique case of spontaneous rupture and complete disappearance of a known sella-suprasellar cyst associated with a severe headache syndrome, followed by cyst reaccumulation requiring surgery. Although this phenomenon is well accepted, to our knowledge, this is the first report of the complete disappearance of a Rathke's cyst presenting with the classic syndrome. Furthermore, it was remarkable how quickly it recurred and became symptomatic, providing evidence that an “empty sella syndrome” may indeed need clinical follow-up.